Medical student attachments in private practice — The experience and views of the family practitioners - D. O’Mahony (South African Family Practice)
Background: Medical student attachments with family/general practitioners (GPs) in non-academic or private practice are a valued resource in the undergraduate teaching of Family Medicine. This study describes the experience and views of GPs in private practice with final-year medical student attachments from the University of Transkei.